2011
DOI: 10.1007/s10198-011-0351-x
|View full text |Cite
|
Sign up to set email alerts
|

Valuing EQ-5D using Time Trade-Off in France

Abstract: This study provides the French value set of the EQ-5D based on the stated preferences of the French general public facilitating cost-effectiveness analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
165
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(176 citation statements)
references
References 16 publications
7
165
0
Order By: Relevance
“…These countries and regions were used: the United Kingdom 15 , the United States 16 , Canada 17 , Denmark 33 , France 24 , Germany 34 , Japan 35 , the Netherlands 36 , and Spain 37 . Each country's original valuation study developed its own mathematical model for determining country-specific tariffs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These countries and regions were used: the United Kingdom 15 , the United States 16 , Canada 17 , Denmark 33 , France 24 , Germany 34 , Japan 35 , the Netherlands 36 , and Spain 37 . Each country's original valuation study developed its own mathematical model for determining country-specific tariffs.…”
Section: Methodsmentioning
confidence: 99%
“…For example, a French valuation study found that French respondents weighted problems in the mobility, self-care, and usual activity parameters more heavily than did U.K. respondents 24 . A comparison of standardized EQ-5D-3L data across countries found that prior living standards (per-capita gross domestic product) correlated the most with the EQ visual analogue scale scores (Spearman rank correlation: 0.58).…”
Section: Introductionmentioning
confidence: 99%
“…For countries without an own national value set the EuroQol group recommends the use of a value set based on geographic proximity. Therefore, in the case of Switzerland, the German [11] or French [12] value sets may be considered. However, as almost 23% (2011) of the population living permanently in Switzerland are foreigners, most of whom come from other European countries, the European Union [13] value set may also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…The most obvious value sets to be used with Swiss patients would be the German [11] and French [12] ones, since Switzerland borders on both Germany and France. These two languages are spoken in different parts of Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…Our study found a difference between both indices in the negative extreme of the theoretical range (-0.28 and -0.53). This difference is explained by the method used for the elicitation of the societal preference values to derive the value set: time tradeoff in French general population for the 3L version [46], and the composite method of time trade-off with discrete choice experiments in the UK general population for the new 5L version [19,25]. Our findings show that the mean EQ-5D-5L indices obtained with both value sets is quite similar (0.88 and 0.83), supporting that the 3L-5L crosswalk is a good interim solution to calculate the EQ-5D-5L…”
Section: Comparison With Prior Studies Evaluating the Eq-5d In Patienmentioning
confidence: 99%